Dual-Domain Synergistic Optimization for Dynamic Reliability Enhancement of Towering Structures in Nonstationary Wind Fields - Leilei Wang; Siyu Wu; Jiaxing Pei; Xinjia Meng (Applied Sciences)
We propose a wind spectrum–response surface dual-domain coupling method to study the reliability optimization of tall structures under the action of unsteady wind fields. Unlike traditional research, the dual-domain coupling analysis can quickly and accurately capture structural response defects and optimize size. The first parametric modeling technology establishes a high-precision finite element model of the movable boom structure by establishing a dual-domain coupling framework of pulsating wind and structural optimization. Using MATLAB (instructional R2024b version), the pulsating wind is simulated with uncertainty. The pulsating wind speeds at different heights are converted into wind loads acting on the net-sealed movable boom structure. Secondly, the boom structure’s dynamic response analysis and response surface optimization design were carried out. The final results show that the maximum value of displacement of the optimized net sealer boom is reduced by about 8.06%, the maximum value of stress is reduced by about 11.04%, and the stiffness is improved through the stress monitoring of the existing structure. It showed that the wind-resistant capability of the boom studied by this method is enhanced, improving the study’s efficiency.